Auxin from the Developing Inflorescence Is Required for the Biosynthesis of Active Gibberellins in Barley Stems - Wolbang, Carla M. (The American Society for Plant Biologists, 2004)
Multiple gibberellins (GAs) were quantified in the stems of intact, decapitated, and decapitated auxin-treated barley (Hordeum vulgare) plants. Removal of the developing inflorescence reduced the endogenous levels of indole-3-acetic acid (IAA), GA(1), and GA(3) and increased the level of GA(29) in internodal and nodal tissues below the site of excision. Application of IAA to the excised stump restored GA levels to normal in almost all cases. The conversion of [(14)C]GA(20) to bioactive [(14)C]GA(1) and of [(14)C]GA(5) to bioactive [(14)C]GA(3) was reduced by decapitation, and IAA application was able to restore conversion rates back to the levels found in intact plants. The amount of mRNA for the principal vegetative 3-oxidase (converting GA(20) to GA(1), and GA(5) to GA(3)) was decreased in decapitated plants and restored by IAA application. The results indicate that the inflorescence of barley is a source of IAA that is transported basipetally into the internodes and nodes where bioactive GA(1) and GA(3) are biosynthesized. Thus, IAA is required for normal GA biosynthesis in stems, acting at multiple steps in the latter part of the pathway.